Changes in land use and ecosystem service value in desert areas of China after reform and opening up - Ba, Zhidan; Du, Huishi; Hasi, Eerdun; Lu, Xiaoling (Frontiers in Earth Science, 2023)
Desert areas of China have important ecological functions, so analyzing changing characteristics of ecosystem service values in this region is important for sustainable development. Using land use change data for desert areas from 1978 to 2022, this paper combined equivalent factor method and actual situation of the study area to revise value coefficients of ecosystem services and study characteristics of land use and ecosystem service value changes after reform and opening up. The results showed that after reform and opening up, area of plough, water and other lands in the study area decreased, while grassland, forest, construction land and sandy land increased. The conversion of land use type mainly occurred as conversion of grassland and other lands to other land use types. The value of ecosystem services increased, increasing by 19.63 × 10 8 CNY, From perspective of land use type in 2022, the ecosystem service value of grassland was the highest, reaching 12.19 × 10 8 CNY, an increase of 11.73×10 8 CNY compared with the early stage of reform and opening up.From the perspective of ecosystem service types in 2022, the value of maintaining soil ecological services was the highest, reaching 3.07×10 8 CNY, an increase of 2.97×10 8 CNY compared with beginning of reform and opening up. From the perspective of ecological sensitivity index, the sensitivity index results for ecosystem service value in the study area were all <1, and the research results were credible. From the perspective of land ecological coordination degree, the overall land ecological coordination degree in the study area was at a moderate coordination level, indicating that land use change did not lead to environmental deterioration, but there was a crisis. Therefore, increasing and maintaining ecological land is the key to improving ESV in the study area.